Use of balloon angioplasty for patients with intracranial large atherosclerotic acute ischemic stroke and cerebral cavernous malformation: a case report - Wang, Yiwan; Wang, Tianyu; Liang, Jiangmin (Frontiers in Neurology, 2025)
Thus far, clinical data relating to the treatment of cerebral cavernous malformation (CCM) patients with acute stroke (AIS) are incredibly scare due to the low incidence of CCM. Furthermore, the safety profile of using tissue plasminogen activator, the only drug approved for AIS treatment within 4.5 h, remains controversial in patients with CCM. Recently, balloon angioplasty has been reported as a successful treatment for intracranial large atherosclerotic AIS patients. In our department, we treated a patient with intracranial large atherosclerotic AIS and CCM using balloon angioplasty, resulting in a positive outcome. Here, we discuss the safety and efficiency of balloon angioplasty for the treatment of intracranial large atherosclerotic AIS in patients with CCM. In conclusion, we suggest that balloon angioplasty may be a potentially safe and effective treatment for intracranial large atherosclerotic AIS patients with CCM. However, further research is needed to explore the use of mechanical revascularization in AIS patients with CCM.